Constrained variational approach for energy derivatives in Intermediate hamiltonian fock-space coupled-cluster theory - Ghosh, Aryya; Gupta, Jitendra; Pal, Sourav; Vaval, Nayana (Chemical Physics, 2012)
Fock-space multi-reference coupled cluster theory is an efficient method for electronic structure of nearly degenerate cases. However, it suffers from the intruder state problem for large model space. The intermediate Hamiltonian formulation eliminates intruder state problem and helps in the convergence of equations. In this paper we have implemented intermediate Hamiltonian approach in Fock-space coupled cluster method for the response properties. We test our method for the dipole moments of doublet radicals. We report dipole moments of CN, SF and NS radicals. (C) 2011 Elsevier B. V. All rights reserved.
Keywords: Constrained variational approach; Fock-space multi-reference coupled cluster; Intermediate Hamiltonian theory; Response approach

Equation-of-motion coupled-cluster method for the study of shape resonance - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Journal of Chemical Physics, 2012)
The equation-of-motion coupled-cluster method (EOM-CC) is applied for the first time to calculate the energy and width of a shape resonance in an electron-molecule scattering. The procedure is based on inclusion of complex absorbing potential with EOM-CC theory. We have applied this method to investigate the shape resonance in e(-)N(2), e(-)CO, and e(-)C(2)H(2). (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4729464]

CAP/EOM-CCSD method for the study of potential curves of resonant states - Ghosh, Aryya; Karne, Anagha S.; Pal, Sourav; Vaval, Nayana (Physical Chemistry Chemical Physics, 2013)
The equation-of-motion coupled-cluster (EOM-CC) method along with the complex absorbing potential (CAP) is used for the study of resonance in e(-)-N-2 and e(-)-CO. Resonance position and width are studied as a function of bond length. We report the potential curves (PC) of the resonance states.

Extended coupled cluster through nth perturbation order for molecular response properties: a comparative study - Gupta, Jitendra; Manohar, Prashant Uday; Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2013)
In this paper, we have presented and analyzed the extended coupled cluster (ECC) energy functional, truncated up to nth perturbation order in which expansion is limit to operators of the single and double excitations. The expression for the first order energy derivatives based on the above truncation schemes has been derived and numerically analyzed. We have done a comparative study for dipole moment in various perturbative ECC (n) methods (2 <= n <= 5) for three systems (HF, H2O and BH) at equilibrium geometry. We have particularly studied two variants of ECC (4) and ECC (5*) method for stretched geometry. We have analyzed the contribution of important terms present in ECC functional based on perturbative argument. We have compared our results with standard coupled cluster (CCSD) as well as cubic truncated ECC and also benchmarked with the full CI results wherever available. (c) 2013 Elsevier B.V. All rights reserved.
Keywords: Dipole moment; Energy functional; Extended coupled cluster

Interatomic coulombic decay in (HF)n,(n=2-3) clusters using CAP/EOM-CCSD method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2013)
The equation-of-motion coupled-cluster method along with the complex absorbing potential has been applied to study the interatomic Coulombic decay mechanism in hydrogen-bonded clusters. We have applied this method to calculate the lifetime of the F 2s inner-valence ionised state of (HF)(n) (n = 2-3) clusters. The lifetime is found to be very short and decreases substantially with increasing the number of HF monomer.
Keywords: complex absorbing potential (CAP); equation-of-motion coupled-cluster (EOM-CC); HF clusters; interatomic Coulombic decay (ICD)

Study of interatomic coulombic decay of Ne(H2O)(n) (n=1,3) clusters using equation-of-motion coupled-cluster method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Journal of Chemical Physics, 2013)
Interatomic Coulombic decay (ICD) is an efficient and ultrafast radiationless decay mechanism which can be initiated by removal of an electron from the inner-valence shell of an atom or molecule. Generally, the ICD mechanism is prevailed in weakly bound clusters. A very promising approach, known as CAP/EOM-CC, consists of the combination of complex absorbing potential (CAP) with the equation-of-motion coupled-cluster (EOM-CC) method, is applied for the first time to study the nature of the ICD mechanism. We have applied this technique to determine the lifetime of an auto-ionized, inner-valence excited state of the NeH2O, Ne(H2O)(2), and Ne(H2O)(3) systems. The lifetime is found to be very short and decreases significantly with the number of neighboring water molecules. (C) 2013 AIP Publishing LLC.

Complex absorbing potential based equation-of-motion coupled cluster method for the potential energy curve of CO2- anion - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav; Bartlett, Rodney J. (Journal of Chemical Physics, 2014)
The equation-of-motion coupled cluster method employing the complex absorbing potential has been used to investigate the low energy electron scattering by CO2. We have studied the potential energy curve for the (2)Pi(u) resonance states of CO2- upon bending as well as symmetric and asymmetric stretching of the molecule. Specifically, we have stretched the C-O bond length from 1.1 angstrom to 1.5 angstrom and the bending angles are changed between 180 degrees and 132 degrees. Upon bending, the low energy (2)Pi(u) resonance state is split into two components, i.e., (2)A(1), B-2(1) due to the Renner-Teller effect, which behave differently as the molecule is bent. (c) 2014 AIP Publishing LLC.

Geometry-dependent lifetime of Interatomic coulombic decay using equation-of-motion coupled cluster method - Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2014)
Electronically excited atom or molecule in an environment can relax via transferring its excess energy to the neighboring atoms or molecules. The process is called Interatomic or Intermolecular coulombic decay (ICD). The ICD is a fast decay process in environment. Generally, the ICD mechanism predominates in weakly bound clusters. In this paper, we have applied the complex absorbing potential approach/equation-of-motion coupled cluster (CAP/EOMCCSD) method which is a combination of CAP and EOMCC approach to study the lifetime of ICD at various geometries of the molecules. We have applied this method to calculate the lifetime of ICD in Ne-X; X = Ne, Mg, Ar, systems. We compare our results with other theoretical and experimental results available in literature. (C) 2014 AIP Publishing LLC.

Relativistic equation-of-motion coupled-cluster method for the double-ionization potentials of closed-shell atoms - Pathak, Himadri; Ghosh, Aryya; Sahoo, B. K.; Das, B. P.; Vaval, Nayana; Pal, Sourav (Physical Review A, 2014)

Lifetime of inner-shell hole states of Ar (2p) and Kr (3d) using equation-of-motion coupled cluster method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Journal of Chemical Physics, 2015)

Auger decay rates of core hole states using equation of motion coupled cluster method - Ghosh, Aryya; Vaval, Nayana; Pal, Sourav (Chemical Physics, 2017)
The recent development of Linac coherent light source high intense X-ray laser makes it possible to create double core ionization in the molecule. The generation of double core hole state and its decay is identified by Auger spectroscopy. The decay of this double core hole (DCH) states can be used as a powerful spectroscopic tool in chemical analysis. In the present work, we have implemented a promising approach, known as CAP-EOMCC method, which is a combination of complex absorbing potential (CAP) and equation -of-motion coupled cluster (EOMCC) approach to calculate the lifetime of single and double core hole states. We have applied this method to calculate the lifetime of the single core hole (K-LL) and double core hole (KK-KLL) states of CH4, NH3 and HF molecules. The predicted lifetime is found to be extremely short. (C) 2016 Elsevier B.V. All rights reserved.

Interatomic Coulombic decay in Neon-Helium cluster: a complex absorbing potential based equation-of-motion coupled cluster investigation - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2021)
The interatomic Coulombic decay (ICD) of the Ne(2s(-1)) and Ne(2s(-1)2p(-1)) states in neon-helium dimer is studied using highly accurate complex absorbing potential based equation-of-motion coupled cluster (CAP-EOMCC) method. The ICD decay process for the Ne(2s(-1)) state in neon-helium dimer is closed at its equilibrium bond distance. However, the decay channel is open at large bond distance of 6.2 angstrom. The decay channel for the double ionised Ne(2s(-1)2p(-1)) state is open at 3.46 angstrom. From our calculations, we have noticed that the decay rate of Ne(2s(-1)2p(-1)) state in neon-helium dimer is four times faster compared to the Ne(2s(-1)) state. We have also investigated how the decay rate of Ne(2s(-1)) state in neon-helium cluster varies in the presence of different helium environment. [GRAPHICS] .
Keywords: double ionised state; equation-of-motion coupled cluster (EOMCC); He droplet; interatomic Coulombic decay (ICD)

Decay processes in cationic alkali metals in microsolvated clusters: a complex absorbing potential based equation-of-motion coupled cluster investigation - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Theory and Computation, 2022)
We have employed the highly accurate complex absorbing potential based ionization potential equation-of-motion coupled cluster singles and doubles (CAP-IP-EOM-CCSD) method to study the various intermolecular decay processes in ionized metals (Li+, Na+, K+) microsolvated by water molecules. For the Li atom, the electron is ionized from the 1s subshell. However, for Na and K atoms, the electron is ionized from 2s and both 2s and 2p subshells, respectively. We have investigated decay processes for the Li+-(H2O)(n) (n = 1-3) systems, as well as Na+-(H2O)(n) (n = 1, 2), and K+-H2O. The lithium cation in water can decay only via electron transfer mediated decay (ETMD) as there are no valence electrons in lithium. We have investigated how the various decay processes change in the presence of different alkali metal atoms and how the increasing number of water molecules play a significant role in the decay of microsolvated systems. To see the effect of the environment, we have studied Li+-NH3 in comparison to Li+-H2O. In the case of Na+-H2O, we have studied the impact of bond distance on the decay width. The effect of polarization on decay width was checked for the X+-H2O (X = Li, Na) systems. We used the PCM model to study the polarization effect. We have compared our results with existing theoretical and experimental results wherever available in the literature.

Effect of charge and solvation shell on non-radiative decay processes in s-block cationic metal ion water clusters - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2023)
Intermolecular Coulombic decay or electron transfer-mediated decay are the autoionization processes through which a molecule can relax. This relaxation is only possible if the inner valence's ionization potential (IP) exceeds the system's double ionization potential (DIP). To study the effects of charge and solvation shell, we have calculated the IP, DIP values, and lifetime of Na-2s and Mg-2s temporary bound states in various optimized structures of Na+-(H2O)(n) and Mg2+-(H2O)(n) (n = 1-5) micro-solvated clusters, where n water molecules are distributed in a way that some are directly bound to the metal ion and the rest to the water molecules. The first and second solvation shells are the names for the former and the latter water-binding positions, respectively. For a given n, the lifetime of decaying states is longer when water molecules are in the second solvation shell. We found that the Mg-2p state can decay for all n values in Mg2+-(H2O)(n) clusters, whereas the Na-2p state's decay is possible for n >= 2 in Na+-(H2O)(n) clusters. Our findings highlight the influence of metal ions' charge, different solvation shell structures, and the number of water molecules on the decay rate. These systems are relevant to the human body, which makes this study significant.

Enhancing diradical character of chichibabin's hydrocarbon through fluoride substitution - Kundu, Gargi; Dash, Soumya Ranjan; Kumar, Ravi; Vanka, Kumar; Ghosh, Aryya; Sen, Sakya S. (ChemPlusChem, 2023)
In this work, 5-SIDipp [SIDipp=1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] (1) derived Chichibabin's hydrocarbon with an octafluorobiphenylene spacer (3) has been reported. The addition of two equivalents of 5-SIDipp with decafluorobiphenyl in presence of BF3 gives the double C-F bond activated imidazolium salt with two tetrafluoroborate anions, 2. Further reduction of 2 gives the fluorine substituted 5-SIDipp based Chichibabin's hydrocarbon, 3. Quantum chemical calculations suggested a singlet state of 3 with a singlet-triplet energy gap (?ES-T) of 3.7 kcal mol(-1), which is substantially lower with respect to the hydrogen substituted NHC-based Chichibabin's hydrocarbons (10.7 kcal mol(-1), B3LYP). As a result, the diradical character (y) of 3 (y=0.62) is also noticeably higher than the hydrogen substituted CHs (y=0.41-0.43). The ?ES-T was found to be higher in CASSCF (22.24 kcal mol(-1)) and CASPT2 (11.17 kcal mol(-1)) for 3 and the diradical character (d) is 44.6 %.
Keywords: C-F Bond Activation; Chichibabin & PRIME; DFT; N-Heterocyclic carbene; s Hydrocarbon

Relaxation of the 2a1 ionized water dimer: an interplay of intermolecular Coulombic decay (ICD) and proton transfer processes - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Journal of Chemical Physics, 2024)
This article investigates the relaxation dynamics of the ionized 2a(1) state of a water molecule within a water dimer. The study was motivated by findings from two previous pieces of research that focused on the relaxation behaviors of the inner-valence ionized water dimer. The present study discloses an observation indicating that water dimers display specific fragmentation patterns following inner-valence ionization, depending on the position of the vacancy. Vacancies were created in the 2a(1) state of the proton-donating water molecule (PDWM) and proton-accepting water molecule (PAWM). Utilizing Born-Oppenheimer molecular dynamics simulations, the propagation of the 2a(1) ionized state was carried out for both scenarios. The results revealed proton transfer occurred when the vacancy resided in the PDWM, accompanied by the closing of decay channels for O-H bond distance (RO-H) > 1.187 & Aring; (matching Richter et al.'s findings). Conversely, when vacancy was on PAWM, we observed no closing of decay channels (aligning with Jahnke et al.'s findings). This difference translates to distinct fragmentation pathways. In PDWM cases, 2a(1) state ionization leads to H3O+ -OH center dot formation. In contrast, PAWM vacancies result in decay pathways leading to H2O+-H(2)O(+ )products.

Unprecedented C-F bond cleavage in perfluoronaphthalene during cobaltocene reduction - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Sangole, Mayur; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Singh, Kirandeep; Sen, Sakya S. (DALTON TRANSACTIONS, 2024)

Charge transfer effect on relaxation mechanism in hydrated pyrrole-water systems following N-2s ionization - Kumar, Ravi; Bhattacharjee, Kankana; Ghosh, Aryya; Vaval, Nayana (ChemPhysChem, 2025)
This study investigates the relaxation mechanisms of pyrrole and pyrrole-water clusters (C4H5N-(H2O)n, where n=0-3 \${n = 0 - 3}\$ ) following N-2s ionization of pyrrole. Using various theoretical methods, we focus on the influence of water molecules and charge transfer on these non-radiative relaxation pathways. Our simulations included pyrrole solvated in 494 explicit water molecules equilibrated at 300 K and also employed a polarizable continuum model (PCM) to make the system more realistic and gain additional insights. In hydrated environments, the hydrogen bonding network between pyrrole and surrounding water molecules facilitates enhanced non-radiative relaxation pathways following inner valence ionization. Since these are hydrogen bonding systems, we have explored the possibility of proton transfer, which could occur in conjunction with other electronic decay processes.
Keywords: ab initio-calculations; auger decay; charge transfer; proton transfer; pyrrole

Kekule diradicaloid with a naphthalene spacer - Kundu, Gargi; Pramanik, Debjit; Dash, Soumya Ranjan; Kumar, Ravi; Tothadi, Srinu; Ghosh, Aryya; Vanka, Kumar; Sen, Sakya S. (Organometallics, 2026)
The availability of a diverse array of carbenes led to the generation of a catalog of carbene based Kekule diradicaloids, but the linker in such molecules is mostly limited to phenylene or biphenylene. Here we have prepared a closed-shell Kekule diradicaloid (2) separated by a naphthalene moiety and stabilized by two capping 5-SIDipp [5-SIDipp = 1,3-bis(2,6-diisopropylphenyl)-imidazolin-2-ylidene] from the reduction of the corresponding dication (1). The combined experimental and computational studies confirm that 2 is in a closed-shell singlet state exhibiting a singlet-triplet energy difference (Delta ES-T) of 18.7 kcal/mol, which is considerably lower than Thiele's version (29.1 kcal/mol).

Solvent and pH effects on the ionization energies of bio-organic molecules: a case study of alanine and glycine - Kumar, Ravi; Ghosh, Aryya; Vaval, Nayana (Physical Chemistry Chemical Physics, 2026)
The ionization energies (IEs) and double ionization energies (DIEs) of the amino acids alanine and glycine have been studied in the gas phase and a polarizable continuum model (PCM) to account for solvent effects. Amino acids undergo structural modifications, particularly in their functional groups, in response to changes in their chemical environment, such as pH. Four possible different structural forms, neutral (NH2-R-COOH), zwitterionic (NH3+-R-COO-), deprotonated (NH2-R-COO-), and protonated (NH3+-R-COOH), were generated for each amino acid. In this study, we use these four forms to explore the effects of protonation and deprotonation (pH effect) on the IEs of inner-valence states. In amino acids, IEs and DIEs are essential for evaluating the energetic viability of inner-valence-initiated non-radiative decay processes, such as interatomic Coulombic decay (ICD). All IE and DIE values were calculated using the complete active space perturbation theory (CASPT2) method. A comparison is made across gas-phase and PCM environments to assess the impact of solvation. The observed variations in IE and DIE values indicate a lot about alanine and glycine's electronic structure and chemical reactivity under different physiological and environmental conditions (pH effect and solvation), hence improving our understanding of their functional roles in biochemical systems.